Additive manufacturing of metals: a brief review of the characteristic microstructures and properties of steels, Ti-6Al-4V and high-entropy alloys. Issue 1 (31st December 2017) - Gorsse, Stéphane; Hutchinson, Christopher; Gouné, Mohamed; Banerjee, Rajarshi
Abstract: We present a brief review of the microstructures and mechanical properties of selected metallic alloys processed by additive manufacturing (AM). Three different alloys, covering a large range of technology readiness levels, are selected to illustrate particular microstructural features developed by AM and clarify the engineering paradigm relating process–microstructure–property. With Ti-6Al-4V the emphasis is placed on the formation of metallurgical defects and microstructures induced by AM and their role on mechanical properties. The effects of the large in-built dislocation density, surface roughness and build atmosphere on mechanical and damage properties are discussed using steels. The impact of rapid solidification inherent to AM on phase selection is highlighted for high-entropy alloys. Using property maps, published mechanical properties of additive manufactured alloys are graphically summarized and compared to conventionally processed counterparts. Abstract :